The Syrian conflict in the context of the confrontation between regional and global players - Tanagozov, С.Д.; Ibragimova, Г.Е. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
This paper identifies the geopolitical interests of the main actors in the Syrian conflict by analyzing their actions. Based on the analysis of sources and scientific publications, the main geopolitical, economic, and military interests of the following parties to the conflict are identified: the United States, the Russian Federation, Iran, Turkey, and the European Union (Germany and France). The authors' research work is based on mapping analysis of the actions of the main actors of the conflict. The conflict is considered simultaneously in several planes, namely: geopolitical influence, conflict resolution, economic influence, and refugee problems. The combination of these aspects makes it possible to identify the main positions of the parties to the conflict, which in turn makes it possible to predict the situation for the near future. In general, it should be recognized that the conclusions of the work correspond to the results of other research papers that claim that the conflict is at an impasse, the resolution of which cannot be in the plane of military operations. However, the authors come to this conclusion through mapping analysis, which only confirms the correctness of such conclusions. Consequently, the novelty of the work lies in the fact that using a different research method, the authors came to the same conclusions as other researchers, which reinforces the overall research significance of such studies. Special attention was also paid to the statistical processing of the situation with Syrian refugees. On the basis of statistical data, the authors have established the main patterns of the movement of refugee flows from Syria, as well as prepared comparative graphs that clearly demonstrate the degree of participation of a particular country in this issue.